Pengaruh Celebrity Endorser dan Customer Experience Terhadap Repurchase Intention Dengan Customer Satisfaction Sebagai Variabel Mediasi Pada Produk Skincare Skintific (Studi Kasus Pengguna Produk Skincare Skintific di Kota Malang) - Septiani, Linda; Diana, Nur; Rahmawati, Rahmawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to determine and analyze the effect of celebrity endorser and customer experience on repurchase intention mediated by customer satisfaction Skintific Skincare Products for consumers of skincare Skintific products in Malang City. The type of research used is quantitative research with the method of distributing questionnaires, using the Malhotra formula because the population of Skintific users is not known with certainly with sample calcultions using non-probability sampling methods with purposive sampling techniques. The sample in this study amounted to 100 respondents and data processing using the Smart-PLS. This study has met the requirements of validity and reliability. The data analysis used in this study is the descriptive statistical method tests, linierity assumption tests,partial least square (PLS): measurement model (outer model), structural model (inner model) and hypothesis testing. The variables used in this study are the dependent variable of repurchase intention, the independent variables are celebrity endorser and customer experience and intervening variable are customer satisfaction. The results of this study indicate that celebrity endorser and customer experience have no significant effect on repurchase intention, celebrity endorsers and customer experience have a significant effect on customer satisfaction. Customer satisfaction can mediate celebrity endorsers and customer experience on repurchase intention  Keywords: Celebrity Endorser, Customer Experience, Repurchase Intention, Customer Satisfaction